2020
DOI: 10.1038/s41598-020-67273-2
|View full text |Cite
|
Sign up to set email alerts
|

Clear aligners for maxillary anterior en masse retraction: a 3D finite element study

Abstract: tang 1,2 ✉ to evaluate tooth behaviours under various maxillary incisor retraction protocols for clear aligner therapy. A three-dimensional finite element model of maxillary dentition was constructed for first premolar extraction. A loading method was developed to mimic the mode of action of clear aligners for incisor en masse retraction. Three protocols with different amounts of retraction and intrusion on incisors were designed. Initial tooth displacements and stresses on periodontal ligaments were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…Ironically, the magnitudes of tooth displacement in this study were on the order of micrometers (eg, 0.02 Angle Orthodontist, Vol 00, No 00, 0000 mm), which was not close to 0.25 mm (the amount of anterior retraction). However, the results were in agreement with Jones et al 14 (tooth displacements ranged from 0.012 to 0.133 mm) and with a recent finite element study on clear aligners by Jiang et al 15 This inconsistency (0.02 vs 0.25 mm) may be attributed to the fact that initial displacement tendency, and not biological displacement, was determined through FEA. For biological displacement, it would take about 2-4 weeks for alveolar remodeling to achieve the actual tooth movement (0.25 mm).…”
Section: Discussionsupporting
confidence: 91%
“…Ironically, the magnitudes of tooth displacement in this study were on the order of micrometers (eg, 0.02 Angle Orthodontist, Vol 00, No 00, 0000 mm), which was not close to 0.25 mm (the amount of anterior retraction). However, the results were in agreement with Jones et al 14 (tooth displacements ranged from 0.012 to 0.133 mm) and with a recent finite element study on clear aligners by Jiang et al 15 This inconsistency (0.02 vs 0.25 mm) may be attributed to the fact that initial displacement tendency, and not biological displacement, was determined through FEA. For biological displacement, it would take about 2-4 weeks for alveolar remodeling to achieve the actual tooth movement (0.25 mm).…”
Section: Discussionsupporting
confidence: 91%
“…The ndings of the study revealed that the maxillary anterior teeth had lingual and distal tipping movements accompanied by occlusal extrusion, and the maxillary posterior teeth exhibited mesial tipping movement accompanied by an intrusion trend during the maxillary anterior teeth retraction process. The research results were consistent with clinical experience and close to those of other researchers [9,23,24] which demonstrates the rationality of this research.…”
Section: Research Modeling and Loading Effectivenesssupporting
confidence: 92%
“…The substance was de ned with a continuously homogeneous and isotropic; the orbital oor of the maxillary alveolar bone was a xed constraint. There was frictional interaction between the crown and the CA, with a friction coe cient of 0.2 [23]. Binding restrictions were found between the teeth of the PDL and the alveolar bone.…”
Section: Materials Properties Interaction and Boundary Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, it must be noted that force transmission patterns from aligners are complex and not yet fully understood [31,32]. This owes to the so called "half shell shapes" of aligners and differences in localization of contact areas to teeth and attachments.…”
Section: Discussionmentioning
confidence: 99%